Synthesis and characterization of high ionic conductivity ScSZ core/shell nanocomposites - 薛倩楠 黄小卫 张赫 徐宏 张建星 王良士 (Journal of rare earths, 2017)
High performance solid electrolytes have been widely used in many devices, such as intermediate temperature（650–850 oC） solid oxide fuel cells, oxygen sensors, super capacitors, etc. In order to solve the problem of phase stability and high grain boundary resistance during the working process, the novel core/shell structure ScSZ nanocomposites were successfully prepared by fractional-precipated method. Non core/shell composites were also prepared by co-precipitation at the same Sc/Zr ratio for comparison. high-resolution transmission electron microscopy（HRTEM）, X-ray photoelectron spectroscopy（XPS）, Raman characterization were performed to identify the microstructure and phase configuration of the obtained composites. According to HRTEM, clear rich scandia shell layer of 2–4 nm existed at the edge of each core/shell particle. The HRTEM figures of non core/shell composites were homogeneous without the shell structure. XPS element analysis for core/shell composite indicated that scandium ratio increased and zirconium ratio decreased when heat treatment temperature fell. When the heating temperature fell down to 450 oC, scandium ratio reached nearly 35 mol.%. EIS and DC measurement were taken for both kinds of electrolytes to study the electrochemical properties. The ionic conductivity were 178.2 and 154.4 mS/cm at 850 oC for core/shell and non core/shell electrolytes, respectively. The mechanism of conductivity improvement was also studied. It was predicted that the core/shell interface could improve ionic conductivity by modifying the space-charge regions. This result outlines a novel and potential direction for high-end electrolytes to enhance ionic conductivity.